Exploring issues of identity and belonging in the films of Mira Nair : Salaam Bombay!, Mississippi Masala and Monsoon Wedding - Van Lill, Hilda (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MDram (Drama))--University of Stellenbosch, 2010.